2022
DOI: 10.1161/hypertensionaha.121.17483
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Cardiac Structure and Function in Pediatric Kidney Transplant Recipients

Abstract: Background: Cardiovascular disease results in increased morbidity and mortality in pediatric kidney transplant recipients. Longitudinal changes in cardiac structure and function and the association with blood pressure control over time in pediatric kidney transplant recipients are unknown. Methods: To determine the influence of blood pressure control on cardiac changes following pediatric kidney transplant, we conducted a retrospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Left ventricular mass index showed sustained improvement up to 12 years in post-transplant patients (16). However, LVM continues to increase in posttransplant patients whose hypertension cannot be controlled (16).…”
Section: Discussionmentioning
confidence: 97%
“…Left ventricular mass index showed sustained improvement up to 12 years in post-transplant patients (16). However, LVM continues to increase in posttransplant patients whose hypertension cannot be controlled (16).…”
Section: Discussionmentioning
confidence: 97%
“…However, in another study by Kitzmueller et al, 54 there was a correlation between LVMI and ABPM data at repeated measurement but not at baseline, suggesting that control of BP, that is, change of BP level during longitudinal follow‐up, is important for the maintenance of the myocardial architecture. Moreover, in a recent Canadian study, de Verteuil et al 55 demonstrated improved cardiac structural abnormalities in children following KTx.…”
Section: Complications Of Hypertension In Transplanted Childrenmentioning
confidence: 94%